Dynamics of cerebral blood flow following sertraline treatment in adolescent depression - Ren, Wenyu; Liu, Xiao; Zhang, Zhiwei; Zhang, Xiaoqin; Wu, Wei; Wang, Xingyu; Yu, Zhihui; Liu, Chuan; Yu, Renqiang (Frontiers in Psychiatry, 2025)
BackgroundArterial spin labeling (ASL), a non-invasive magnetic resonance imaging (MRI) technique, has been employed to assess variations in cerebral blood flow (CBF) in adolescents diagnosed with depression. While prior studies have explored CBF abnormalities in depressed adolescents, the specific patterns of CBF changes following pharmacological interventions, particularly with selective serotonin reuptake inhibitors (SSRIs) such as sertraline, remain insufficiently characterized.ObjectiveTo investigate the alterations in CBF induced by an 8-week sertraline treatment in adolescents with depression, and to assess whether baseline CBF can serve as a potential biomarker for predicting treatment response.MethodsA total of 40 adolescents diagnosed with depression and 31 age- and sex-matched healthy controls were enrolled in the study. Among the depressed cohort, 25 participants adhered to the treatment protocol and completed MRI scans. Resting-state functional MRI (rs-fMRI) scans were conducted for all participants, with a subsequent scan for the depression group after 8 weeks of sertraline therapy. Changes in CBF across various brain regions were examined using ASL data. The analysis and processing of ASL data were performed using Statistical Parametric Mapping 12 (SPM12) software and the MATLAB platform. Furthermore, Pearson correlation analysis was employed to examine associations between changes in regional CBF and clinical improvement, as measured by changes in the 17-item Hamilton Depression Rating Scale (HAMD-17) scores.ResultsAt baseline, adolescents with depression exhibited increased CBF in the posterior cuneus and decreased CBF in the middle temporal gyrus (MTG), right middle orbitofrontal gyrus, and the left middle frontal gyrus (MFG), compared to healthy controls. After 8 weeks of sertraline treatment, patients showed increased CBF in the right insula and decreased in the right MTG. Notably, baseline CBF in the left orbitofrontal gyrus was positively correlated with the magnitude of clinical improvement (i.e., reduction in HAMD-17 scores).ConclusionThe findings reveal significant differences in CBF between adolescents with depression and healthy controls. Moreover, alterations in CBF were observed in specific brain regions after an 8-week treatment regimen with sertraline, suggesting that these areas may be pivotal in the therapeutic effects of sertraline for treating adolescent depression. A decrease in HAMD-17 scores in the majority of treated patients underscores the efficacy of sertraline therapy. Notably, the change in HAMD scores from pre- to post-treatment was positively correlated with baseline CBF in the left MFG, indicating the potential of this region as a prognostic indicator.